2008
DOI: 10.1161/circ.118.suppl_18.s_341-a
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1514: RXP-E: A Connexin43-Binding Peptide that Prevents Action Potential Propagation Block

Abstract: Gap junctions (GJ’s) provide a low resistance pathway for cardiac electrical propagation. The role of GJ regulation in arrhythmias is unclear, partly due to the limited availability of pharmacological tools. Recently, we showed that a peptide called “RXP-E” binds to the carboxyl terminal of connexin43 (Cx43) and prevents chemically-induced uncoupling in Cx43-expressing N2a cells. Here, we used pull-down experiments to show that RXP-E binds to adult cardiac Cx43. Patch-clamp studies revealed that RXP-E prevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…63 Overall insight to this subject: innovation is needed for the production of connexin-based therapeutics, although there is little information about the use of connexin-based therapeutics in the clinic for the treatment of either arrhythmia or any other heart disease with an enhancement of gap-junctional communication (i.e., improvement of lowered conduction) via treatment with a connexinbased therapeutic. [65][66][67] Overall, we, here, demonstrated that not only reduced levels of pCx43 and Cx43 but also their apparent internalizations and lateralizations may be associated with abnormal ventricular repolarization, which in turn leads to long-QT in the Aged-group under insulin resistance, similar to the MetS-group. In this regard, although the underlying mechanisms of these two syndromes include alterations in electrophysiological properties of cardiomyocytes besides changes in the heart tissues, further studies are needed to clarify the exact mechanism responsible for the existence of these changes under insulin resistance.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…63 Overall insight to this subject: innovation is needed for the production of connexin-based therapeutics, although there is little information about the use of connexin-based therapeutics in the clinic for the treatment of either arrhythmia or any other heart disease with an enhancement of gap-junctional communication (i.e., improvement of lowered conduction) via treatment with a connexinbased therapeutic. [65][66][67] Overall, we, here, demonstrated that not only reduced levels of pCx43 and Cx43 but also their apparent internalizations and lateralizations may be associated with abnormal ventricular repolarization, which in turn leads to long-QT in the Aged-group under insulin resistance, similar to the MetS-group. In this regard, although the underlying mechanisms of these two syndromes include alterations in electrophysiological properties of cardiomyocytes besides changes in the heart tissues, further studies are needed to clarify the exact mechanism responsible for the existence of these changes under insulin resistance.…”
Section: Discussionsupporting
confidence: 60%
“…63 Overall insight to this subject: innovation is needed for the production of connexin-based therapeutics, although there is little information about the use of connexin-based therapeutics in the clinic for the treatment of either arrhythmia or any other heart disease with an enhancement of gap-junctional communication (i.e., improvement of lowered conduction) via treatment with a connexin-based therapeutic. 6567…”
Section: Discussionmentioning
confidence: 99%
“…dual whole-cell voltage clamp analysis in pairs of adult cardiac myocytes internally dialysed with a pipette solution buffered at pH 6.2. 19 Initial whole-cell conductances were not significantly different between cardiomyocyte pairs of either genotype (Cx43/KO: 27.2 + 5.2, NS, n ¼ 5; K258stop/KO: 25.3 + 3.6, NS, n ¼ 6; P . 0.05).…”
Section: Effects Of Intracellular Acidification On Adult Cardiomyocyt...mentioning
confidence: 90%
“…17 Cells were used for recording within 8 h after isolation. Details on recording of gap junctional currents can be found in Shibayama et al 18 and Lewandowski et al 19 and in Supplementary material online. Estimation of macroscopic junctional conductance (G j ) and series resistance correction followed methods previously described.…”
Section: Cell Isolation and Dual-patch Electrophysiologymentioning
confidence: 99%
See 1 more Smart Citation